Pengaruh Lingkungan Kerja Non Fisik, Motivasi, dan Beban Kerja terhadap Kinerja Karyawan PT Patriot Intan Abadi - Galuh Reza Dwi Agusta (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to examine employee responses and analyze the influence of non-physical work environment, motivation, and workload on employee performance at PT. Patriot Intan Abadi Unit Hatchery Caringin, Bogor. The method applied is descriptive verifiable with a quantitative approach. Data collection is carried out through a questionnaire that has been tested for validity and reliability to ensure the reliability of the instrument. Data analysis techniques include multiple linear regression, correlation coefficient analysis, determination coefficient (R²), as well as F test and t test to test significance simultaneously or partially between variables. The results of the study showed that all items of the research instrument were valid and reliable. A determination coefficient (R²) of 50% indicates that non-physical work environment, motivation, and workload variables simultaneously contribute to an increase in employee performance by 50%, while the rest is influenced by other factors beyond the scope of the study. The F test shows that the three independent variables together have a significant effect on employee performance. Meanwhile, the results of the t-test showed that partially, each of the variables — non-physical work environment, motivation, and workload — had a positive and significant influence on employee performance. These findings confirm that psychological aspects in the work environment, employee internal motivation, and proper workload management play a strategic role in supporting increased employee productivity and quality of work. Therefore, company management is advised to continue to create an emotionally supportive work atmosphere, pay attention to factors that can motivate employees, and conduct periodic evaluations of workload distribution to maintain balance and avoid fatigue that negatively impacts performance. This research also opens up opportunities for further research that can explore other factors such as leadership, organizational culture, or employee well-being that may play a role in shaping performance in complex work environments.